HUBUNGAN KESEHATAN LINGKUNGAN RUMAH DENGAN KEJADIAN ISPA PADA SISWA SD NEGERI 1 ULAK DEPATI - Wennas .; Sarita Miguna (Universitas Batam, 2019)
Environmental factors that affect human health can come from the air or a small scope such as cigarette smoke in the house, South Sumatra in the Pampangan district, precisely in the village of Ulak Depati. The purpose of this study was to determine the relationship of environmental health with the incidence of ARI in elementary students 1 Ulak Depati. This research is a quantitative type with a descriptive-analytic research design with a cross-sectional approach. The population of this research was 75 students of SD Negeri 1 Ulak Depati and the total technique was used because the sample was less than 100 people. The results of univariate analysis showed that respondents experienced complaints of 56 (74.7%) respondents and did not experience complaints 19 (25.3%) respondents, respondents who answered there was pollution amounting to 52 (69.3%) respondents and None pollution, amounting to 52 (69.3%) of respondents, respondents stated that the area of ventilation in good condition is equal to 56 (74.7%) of respondents and the respondent stated that the area of ventilation in a condition is not good that is equal to 19 (25.3%) of respondents. Respondents stated that the air quality was in good condition in the amount of 49 (65.3%) respondents and the respondents stated that the air quality was in a poor condition that was equal to 26 (34.7%) respondents. The density of solid occupancy is 51 (68.0%) of respondents and the respondent states that the density of occupancy in the solid category is 24 (32.0%) of respondents meaning between environmental pollution to ARI event where Ï value = 0,000 Î± = 0.05 (OR = 14,622 ); 2) There is a significant relationship between the area of ventilation against the ISP event where Ï value = 0,000 Î± = 0.05 (OR = 12,880); 3) There is a significant relationship between air quality and the ISP event where Ï value = 0.004 Î± = 0.05 (OR = 2.778); 4) There is a significant relationship between a meaningful relationship between occupancy density and ARI events where Ï value = 0,000 Î± = 0.05 (OR = 15,220. From the results of the study it can be concluded that there is a significant relationship between the relationship of environmental health with the incidence of ARI in students of SD Negeri 1 Ulak Depati